Клінічний випадок псевдогіпопаратиреозу - Писаренко, С. Г. (Clinical Endocrinology and Endocrine Surgery, 2011)
In this article the clinical case of pseudohypoparathyroidism at the child is described. There were symptoms low lever of calcium in blood, stunting, the wide thorax, the raised lever of parathhormon in blood.